2010
DOI: 10.1523/jneurosci.4367-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Dependent Facilitation of Cav1.3 Ca2+Channels by Densin and Ca2+/Calmodulin-Dependent Protein Kinase II

Abstract: Cav1 (L-type) channels and calmodulin-dependent protein kinase II (CaMKII) are key regulators of Ca2+signaling in neurons. CaMKII directly potentiates the activity of Cav1.2 and Cav1.3 channels, but the underlying molecular mechanisms are incompletely understood. Here, we report that the CaMKII-associated protein densin is required for Ca2+-dependent facilitation of Cav1.3 channels. While neither CaMKII nor densin independently affects Cav1.3 properties in transfected HEK293T cells, the two together augment Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 72 publications
2
105
0
Order By: Relevance
“…Because there are no detectable interactions of CaMKII␣ with the N-terminal LRR domain of densin (densin-T482 splice variant) (9), CaMKII may also interact somewhere between the LRR and C-terminal domains. Consistent with this hypothesis, deletion of a large central domain (residues 483-1377) in a naturally occurring densin splice variant substantially reduced the binding of CaMKII␣ even though this variant retains the C-terminal CaMKII␣ binding domain (12). Therefore, we expressed a family of GST fusion proteins spanning the large central domain of densin in bacteria (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Because there are no detectable interactions of CaMKII␣ with the N-terminal LRR domain of densin (densin-T482 splice variant) (9), CaMKII may also interact somewhere between the LRR and C-terminal domains. Consistent with this hypothesis, deletion of a large central domain (residues 483-1377) in a naturally occurring densin splice variant substantially reduced the binding of CaMKII␣ even though this variant retains the C-terminal CaMKII␣ binding domain (12). Therefore, we expressed a family of GST fusion proteins spanning the large central domain of densin in bacteria (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…For example, although densin-FLC may be expressed only in the perinatal period (6), before CaMKII␣ expression, the IN domain may allow densin-FLC to modulate CaMKII␤. In addition, we previously showed that a natural densin splice variant lacking a large central region containing the densin-IN domain is unable to support CaMKII␣-dependent facilitation of Ca V 1.3 L-type calcium channels (12). A deeper understanding of the expression of densin splice variants in different cell types during development is required to fully appreciate the implications of these findings for CaMKII isoform regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast presynaptic neurotransmitter release in neurons depends on the close coupling of presynaptic Ca V 2 channels to the release machinery. By contrast, Ca V 1.3 and Ca V 1.2 are located postsynaptically predominantly on the cell soma and in the spines and shafts of dendrites in neurons (Di Biase et al, 2008;Jenkins et al, 2010). There they shape neuronal firing and activate Ca 2+ -dependent pathways involved in control of gene expression, termed excitation-transcription coupling .…”
Section: Ca V 1 Channel Familymentioning
confidence: 89%
“…The distal carboxy-terminal domain plays an autoregulatory role in both Ca V 1.3 and Ca V 1.4 channels (Singh et al 2006(Singh et al , 2008, but it is not known whether it is subject to proteolytic processing in vivo. Ca V 1.3 channels are regulated by multiple interacting proteins (Cui et al 2007;Jenkins et al 2010), which may be important in tuning their activity to fit the specific requirements of hair cells transmitting auditory information at different frequencies.…”
Section: Ca V 1 Channels In Excitation-secretion Couplingmentioning
confidence: 99%